2019
DOI: 10.1101/807040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soil microbial communities associated with giant sequoia: How does the world’s largest tree affect some of the world’s smallest organisms?

Abstract: Giant sequoia (Sequoiadendron giganteum) is an iconic conifer that lives in relic 3 populations on the western slopes of the California Sierra Nevada. In these settings it is 4 unusual among the dominant trees in that it associates with arbuscular mycorrhizal fungi 5 rather than ectomycorrhizal fungi. However, it is unclear whether differences in 6 microbial associations extends more broadly to non-mycorrhizal components of the soil 7 microbial community. To address this question we characterized microbiomes a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…A couple recent studies have found an increase in dominance of the sister genus Geminibasidium , including a study of a Pinus ponderosa forest in the American Pacific Northwest (Pulido-Chavez et al, 2021) and a study of Larix and Betula dominated forests in northeastern China (Yang et al, 2020). Geminibasidium was also present at 0.05% sequence abundance, the same amount as our pre-fire soil, in an unburned giant sequoia forest (Carey et al, 2019). While Geminibasidiomycetes are positively selected for by fire (Figure 6) likely due to their thermotolerance and xerotolerance (Nguyen et al, 2013), they have been missed by existing descriptions of pyrophilous fungi that are mainly based on fruiting body surveys (McMullan-Fisher et al, 2011).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A couple recent studies have found an increase in dominance of the sister genus Geminibasidium , including a study of a Pinus ponderosa forest in the American Pacific Northwest (Pulido-Chavez et al, 2021) and a study of Larix and Betula dominated forests in northeastern China (Yang et al, 2020). Geminibasidium was also present at 0.05% sequence abundance, the same amount as our pre-fire soil, in an unburned giant sequoia forest (Carey et al, 2019). While Geminibasidiomycetes are positively selected for by fire (Figure 6) likely due to their thermotolerance and xerotolerance (Nguyen et al, 2013), they have been missed by existing descriptions of pyrophilous fungi that are mainly based on fruiting body surveys (McMullan-Fisher et al, 2011).…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, a study of the microbial composition of the coastal redwood’s sister genus, the giant sequoia ( Sequoiadendron giganteum), also showed domination by Bradyrhizobium and Sinobacteraceae sp. of the Proteobacteria (Carey et al, 2019). The similarities with the giant sequoia soil communities also extend to fungi, with Hygrocybe dominating both our redwood forests pre-fire and in the giant sequoia forest.…”
Section: Discussionmentioning
confidence: 99%